Vanadium(V) complexes with substituted 1,5-bis(2- hydroxybenzaldehyde)carbohydrazones and their use as catalyst precursors in oxidation of cyclohexane - Dragancea, Diana (2017)
Six dinuclear vanadium(V) complexes have been synthesized: NH4[(VO2)(2)((LH)-L-H)] (NH4[1]), NH4[(VO2)(2)((LH)-L-tBu)] (NH4[2]), NH4[(VO2)(2)((LH)-L-Cl)] (NH4[3]), [(VO2)(2)(VO) ((LH)-L-H) (CH3O)] (4), [(VO2) (VO) (t-BuLH) (C2H5O)] (5), and [ (VO2) (VO) (Cl-LH) (CH3O)(CH3OH/H2O)] (6) (where (LH4)-L-H = 1,5-bis(2-hydroxybenzaldehyde)carb ohydrazon e, t-BuLH4 = 1,5-bis(3,5-di-tert-butyl-2-hydroxybenzaldehyde) carbohydrazone, and (LH4)-L-cl = 1,5-bis(3,5-dichloro-2-hydroxybenzaldehyde)carbohydrazone). The structures of NH4[1] and 4-6 have been determined by X-ray diffraction (XRD) analysis. In all complexes, the triply deprotonated ligand accommodates two V ions, using two different binding sites ONN and ONO separated by a diazine unit -N-N-. In two pockets of NH4[1], two identical VO2+ entities are present, whereas, in those of 4-6, two different VO2+ and VO3+ are bound. The highest oxidation state of V ions was corroborated by X-ray data, indicating the presence of alkoxido ligand bound to VO3+ in 4-6, charge density measurements on 4, magnetic susceptibility, NMR spectroscopy, spectroelectrochemistry, and density functional theory (DFT) calculations. All four complexes characterized by XRD form dimeric associates in the solid state, which, however, do not remain intact in solution. Compounds NH4[1], NH4[2], and 4-6 were applied as alternative selective homogeneous catalysts for the industrially significant oxidation of cyclohexane to cyclohexanol and cyclohexanone. The peroxidative (with tert-butyl hydroperoxide, TBHP) oxidation of cyclohexane was performed under solvent -free and additive -free conditions and under low-power microwave (MW) irradiation. Cyclohexanol and cyclohexanone were the only products obtained (high selectivity), after 1.5 h of MW irradiation. Theoretical calculations suggest a key mechanistic role played by the carbohydrazone ligand, which can undergo reduction, instead of the metal itself, to form an active reduced form of the catalyst.